The Determinants of CCMA Effectiveness as Perceived by Employees in a Selected South African Municipality - Nosiphokazi Heroine Sigauke; Ronald Machingambi; Christiana Kappo-Abidemi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
The CCMA was established to implement the required fundamental changes in South African labor relations. The Labor Relations Act 66 of 1995 sets CCMA's expectations regarding dispute resolutions and collective bargaining. The South African CCMA is considered the largest labor dispute agency in the world in terms of referrals, with 3,632,085 cases since its inception. This study focused on public service employees’ perceptions of the effectiveness of CCMA based on participants’ demographic information. The study adopted a quantitative approach using a self-developed Likert scale questionnaire for data collection. The population consisted of Mbombela municipality employees, and the purposive non-probability sampling method was used to select study participants who consulted the CCMA before being eligible to participate. Limited  studies conducted in South Africa have explored employees’ perceptions of CCMA activities. Hence, this study aims to contribute to the existing knowledge of South African labor dispute resolution mechanisms and employees’ perceptions of the largest labor dispute resolution in the continent. The questionnaire included 24 items, and factor analysis was used to identify related items. Linear regression is used to analyze public service employees’ perceptions of the effectiveness of the CCMA based on the identified components using participants’ demographic information. The results show no significant differences in the perceptions of the CCMA's effectiveness based on the gender and educational qualifications of the participants. Significant differences exist across the ages and years of working experience. The CCMA mandates should be reviewed in line with the new challenges that are encountered in the workplace. The stakeholders are encouraged to make adequate provisions so that the Commission can conduct its mandate to satisfy its clients.